My general manager is warmer than department manager: Stereotypes about senior and junior high-power individuals and their influences on spontaneous trait inference - Yang, Feng; Li, Minyan; Han, Yang; Fan, Xinru; Zhang, Qing (Frontiers in Psychology, 2022)
Previous research suggests that high-power (HP) individuals are stereotyped as positive competence but negative warmth. By subdividing HP individuals into junior and senior HP individuals, the current research conducted five studies to examine the warmth perception differences toward senior and junior HP individuals in Confucian culture and the downstream effects on spontaneous trait inference (STI). By using different paradigms, Study 1 and 2 found that participants tended to perceive junior HP individuals as negative on the warmth dimension and perceive senior HP individuals as positive on the warmth dimension. The following Study 3 and 4 further found that the warmth perception differences toward senior and junior HP individuals had an influence on STI. Specifically, participants were inclined to make STI from behaviors implying negative warmth traits when behavioral actors were junior HP individuals while they were inclined to make STI from behaviors implying positive warmth traits when behavioral actors were senior HP individuals. Additionally, Study 4 found that perceived social responsibility about HP individuals accounted for the power stereotype effects in STI — the more social responsibility participants perceived about senior HP individuals, the stronger power stereotype effects they showed in STI. The final Study 5 revealed that the different power stereotype effects in STI induced by senior and junior HP actors were observed only in Confucian culture, but not in non-Confucian culture. The present research firstly demonstrated that the warmth perceptions about senior and junior produced different influences on STI in Confucian culture, and also enriched the understanding about the culture-specificity of the stereotype content model.